Green Synthesis of Fucoidan-Chitosan Coated Silver Nanoparticles Biocojugates and their Antimicrobial Activity - Divyapriya, S.; Rajathi, K. (Asian Journal of Biological and Life Sciences)
Reliable and environmentally friendly methods for the separation of nanoparticles are urgently needed in the field of nanotechnology. Traditional NP synthesis approaches are costly, harmful and detrimental to the atmosphere. To overcome these challenges, scientists have turned to natural sources such as plants, microorganisms, fungi and biopolymers for synthesizing Silver Nanoparticles (AgNPs), with these sources acting as both reducing and capping agents. Avocado leaves, known for their abundance in antioxidant compounds that protect against free radical damage and disease, are particularly noteworthy in this regard. This study aims to establish the synthesis and formulation of Fucoidan-Chitosan-coated silver nanoparticles using plant extract, with characterization conducted via SEM, EDX, FT-IR and UV-Visible Spectroscopy, along with the evaluation of the antibacterial activity of Ag nanoparticles. Nanoparticle-based therapy has garnered significant attention in the pharmaceutical and biomedical sectors. Functional nanoparticles were produced by coating fucoidan-chitosan onto silver nanoparticles loaded with avocado extract. These nanoparticles were synthesized through green synthesis using avocado leaf extract. The findings revealed that the fucoidan-chitosan coating enhances the stability and dispersibility of AG nanoparticles in aqueous environments, while also conferring antibacterial properties. Notable antibacterial activity of the avocado plant extract-coated AGNPs were observed against various organisms in vitro. The obtained sample holds promise for treating a range of disorders such as cancer, diabetes, cardiovascular diseases and Polycystic Ovary Syndrome (PCOS). The hybrid nanoparticles represent a potential therapeutic agent in cancer therapy, with the active extracts of avocado leaves offering promising medicinal applications.
Keywords: Chitosan; Fucoidan; Persea Americana; Sliver Nanoparticles